Pragmatisasi Pendidikan dalam Dunia Kerja - Malikah, Nurul (Nadwa, 2014)
Vocational education as a part of the National Education system plays a strategic role for the realization of the skilled national labor. Because each vocational graduates is created to become good human resources, in the sense that when they have completed vocational school they able to apply the knowledge. But in fact, the graduates of vocational school is recognized only by itself school and still lack confidence in the business and industrial world. The old model of vocational education has disadvantage, is education model that was conducted unilaterally so that students left behind by the progress of the business/industrial world. Creating creativity and independence of the student is the right answer to avoid dependency and to reduce the unemployment rate. The Awareness of self-development by enhancing the students confidence and self-reliance is an important part to prepare for the long-term goal achievement.